Differences in gut microbiota between silkworms (Bombyx mori) reared on fresh mulberry (Morus alba var. multicaulis) leaves or an artificial diet. Issue 46 (20th July 2018) - Dong, Hui-Ling; Zhang, Sheng-Xiang; Chen, Zhuo-Hua; Tao, Hui; Li, Xue; Qiu, Jian-Feng; Cui, Wen-Zhao; Sima, Yang-Hu; Cui, Wei-Zheng; Xu, Shi-Qing
Abstract : Artificial diets for silkworms have many potential applications and they are important in sericulture. Abstract : Artificial diets for silkworms have many potential applications and they are important in sericulture. However, the challenges of weak larvae and low silk protein synthesis efficiency in silkworms reared on artificial diets have not been resolved. Here, we used high-throughput sequencing to analyse the differences between the gut microbiota of 5th-instar larvae reared on mulberry leaves and larvae reared on an artificial diet. The results showed that at the phylum level, Cyanobacteria, Firmicutes, Proteobacteria, Bacteroidetes and Actinobacteria are the dominant bacteria in the intestines of silkworm larvae of all the strains. But the abundance of dominant bacteria in the gut microbiota differed between the silkworm strains that were reared on mulberry leaves, as well as between the silkworm strains that were reared on the artificial diet, while the gut microbiota diversity was lower in the silkworm strains that were reared on the artificial diet. Prediction of the functions of the gut microbiota in the hosts indicated that there was no significant difference between the silkworm strains that were reared on mulberry leaves, while there were significant differences between silkworm strains reared on the artificial diet. When the silkworm diet changed from mulberry leaves to the artificial diet, changes in gut microbiota in the silkworms affected host nutrient metabolism and immune resistance. These changes may be related to the adaptation of silkworms to their long evolutionary history of eating mulberry leaves.